2020
DOI: 10.1080/19490976.2020.1785803
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-protective effect of a synbiotic combination between Lactobacillus gasseri 505 and a Cudrania tricuspidata leaf extract on colitis-associated colorectal cancer

Abstract: Previously, a synbiotic combination of probiotic Lactobacillus gasseri 505 (LG) and a new prebiotic, Cudrania tricuspidata leaf extract (CT) in fermented milk, designated FCT, showed an in vitro immunomodulatory effect and antioxidant activity. Although synbiotic combination might have cancer-protective effects, these activities have not been fully validated in vivo. Ten-week treatment of LG, CT, or FCT to azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced colitis-associated colorectal cancer (CAC) mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 98 publications
4
67
0
Order By: Relevance
“…This suggests that there is a special connection between probiotics and CRC. In fact, numerous studies have demonstrated the anti-tumor effects of probiotics such as L. acidophilus, L. casei, L. plantarum, and B. longum (13,14). However, before a specific probiotic strain can be considered part of a cancer treatment regimen, its function needs to be assessed in detail (15).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there is a special connection between probiotics and CRC. In fact, numerous studies have demonstrated the anti-tumor effects of probiotics such as L. acidophilus, L. casei, L. plantarum, and B. longum (13,14). However, before a specific probiotic strain can be considered part of a cancer treatment regimen, its function needs to be assessed in detail (15).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high-sugar diet was shown to enhance susceptibility to DSS-colitis via depletion of luminal short chain fatty acids [ 181 ]. Similar to dietary fibers, several probiotics and symbiotic supplementations with dietary fibers also ameliorated disease activity, changed the gut microbiota, and showed SCFA-supporting effects [ 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 ]. These promising reports inspired further studies on the direct effect of SCFA supplementation on experimental colitis.…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…In an AOM/DSS model, this treatment ameliorated the effects of cancer by downregulating pro-inflammatory cytokines (TNF-α, IFN-γ, IL-1β, and IL-6) and anti-apoptotic factors (Bcl-2 and Bcl-xL), and upregulating anti-inflammatory cytokines (IL-4 and IL-10) and pro-apoptotic factors (p53, p21, and Bax). Furthermore, synbiotic treatment decreased the expression of the inflammation-associated enzymes iNOS and COX-2 [ 115 ]. These effects were corroborated by work in a mouse model that demonstrated the ability of this combination to prevent the hepatic toxicity induced by CRC [ 116 ].…”
Section: Synbioticsmentioning
confidence: 99%